The Labor Theory of Value: A Masked Dialogue in the Exchange of Wounds (Papeles, 2020)
Every day we exchange the spent hours of our day. Although the outcome of this meeting is only money, most of us give our work tattooed in coins to others, almost always anonymous, in exchange for objects and services (we imagine the work of others) , offered as merchandise. Centuries ago, this exchange was made between direct producers, since money was hardly used between two people who were close to value dissimilar products, although there was always the doubt about small differences in the exchange of wounds.